Expanding Inpatient Addiction Consult Services Through Accountable Care Organizations for Medicaid Enrollees: A Modeling Study. Issue 5 (8th September 2022) - King, Caroline A.; Cook, Ryan; Korthuis, P. Todd; McCarty, Dennis; Morris, Cynthia D.; Englander, Honora
Abstract : Introduction: Addiction consult services (ACS) care for hospitalized patients with substance use disorder, including opioid use disorder (OUD). Medicaid Accountable Care Organizations (ACOs) could enhance access to ACS. This study extends data from Oregon's only ACS to Oregon's 15 regional Medicaid Coordinated Care Organizations (CCOs) to illustrate the potential value of enhanced in- and out-patient care for hospitalized patients with OUD. The study objectives were to estimate the effects of (1) expanding ACS care through CCOs in Oregon, and (2) increasing community treatment access within CCOs, on post-discharge OUD treatment engagement. Methods: We used a validated Markov model, populated with Oregon Medicaid data from April 2015 to December 2017, to estimate study objectives. Results: Oregon Medicaid patients hospitalized with OUD with care billed to a CCO (n = 5878) included 1298 (22.1%) patients engaged in post-discharge OUD treatment. Simulation of referral to an ACS increased post-discharge OUD treatment engagement to 47.0% (95% confidence interval [CI] 45.7%, 48.3%), or 2684 patients (95% CI 2610, 2758). Ten of fifteen (66.7%) CCOs had fewer than 20% of patients engage in post-discharge OUD care. Without ACS, increasing outpatient treatment such that 20% of patients engage increased the patients engaging in post-discharge OUD care from 12.9% or 296 patients in care at baseline to 20% (95% CI 18.1%, 21.4%) or 453 (95% CI 416, 491). Discussion: ACOs can improve care for patients hospitalized with OUD. Implementing ACS in ACO networks can potentially improve post-discharge OUD treatment engagement, but community treatment systems must be prepared to accept more patients as inpatient addiction care improves.